2001
DOI: 10.1002/app.10127
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behaviors of polypropylene/montmorillonite nanocomposites

Abstract: ABSTRACT:The isothermal crystallization kinetics of polypropylene/montmorillonite (PP/MMT) nanocomposites synthesized via intercalation polymerization were investigated by using differential scanning calorimeter and polarizing optical microscope (POM). The crystallinity of the nanocomposites decreased with the increase of the montmorillonite content, indicating that the MMT layers dispersed in the PP matrices confined the PP chains and hindered the crystallization of the PP chains. The POM photographs showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
3
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(145 citation statements)
references
References 14 publications
10
128
3
4
Order By: Relevance
“…Many studies have shown a nucleating effect of nanoclay for different polymers [16][17][18]. This effect can be used to enhance the mechanical and thermal properties of the polymer.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Many studies have shown a nucleating effect of nanoclay for different polymers [16][17][18]. This effect can be used to enhance the mechanical and thermal properties of the polymer.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Regarding the effect of cooling rate on the crystallization peak temperature (Figure 3), it is found that the crystallization peak temperature range becomes broader and shifts to lower temperatures for sPS and its nanocomposites as the cooling rate increased. When the specimens were cooled quickly, more supercooling was required to initiate crystallization, because the motion of the sPS molecules could not follow the cooling rate [50,51]. With increasing the cooling rate, the crystallization peak temperature corresponding to the maximum crystallization rate shifted to lower temperature, indicating that the lower the cooling rate, the earlier crystallization occurs.…”
Section: Thermal Behaviormentioning
confidence: 99%
“…A decrease in spherulite size and an increase in crystallization rate with augmenting clay content in PP nanocomposites have been reported. [14,20,21] The presence of excessive unreacted organic molecules in the OM has been reported to have detrimental effect on the thermal stability and properties of the composites. [2,[22][23][24] The ammonium head group of the surfactant is susceptible to degradation at the high compounding temperatures and the thermal stability of the organic coating is a serious concern.…”
Section: Introductionmentioning
confidence: 99%